Konsep Ikhlas dalam Al-Qur’an: Analisis Tematik-Komparatif QS. Az-Zumar ayat3 dan QS. Al-Ikhlas ayat 4 dalam Perspektif Tafsir Klasik - Sholikhah, Virdatus; Sassi, Komarudin; ., . (Balai Diklat Keagamaan Bandung, 2025)
This article examines the concept of ikhlas (sincerity) in the Qur’an through a thematic-comparative analysis of QS. Az-Zumar (39):3 and QS. Al-Ikhlas (112):4, drawing on classical Qur’anic exegesis, particularly that of Ibn Kathir, with supporting references to Ath-?abari and Al-Qur?ubi. The study aims to analyze ikhlas as a fundamental principle of tauhid that encompasses both the practical dimension of religious action (fi‘liyyah) and the doctrinal dimension of belief (i‘tiq?diyyah), and to clarify their integrative relationship within Islamic spirituality. Employing a qualitative library-based research design, this study applies thematic and comparative tafsir analysis to explore the theological meanings of the selected verses. The findings indicate that QS. Az-Zumar (39):3 emphasizes ikhlas as the purification of worship from intermediaries and non-divine orientations, while QS. Al-Ikhlas (112):4 affirms the absolute oneness and incomparability of God as the theological foundation of sincere faith. Together, these verses construct a comprehensive understanding of ikhlas that remains relevant for addressing contemporary religious challenges, including digital ostentation, the cult of religious figures, and the transactionalization of worship. This study concludes that ikhlas is not merely an inner disposition of intention, but a direct manifestation of pure monotheism in both belief and religious practice. Keywords: Ikhlas; Tauhid; Thematic Tafsir; QS. Az-Zumar (39):3; QS. Al-Ikhlas (112):4